The Impact of The Internet on Teenage Delinquency - Sulastri, Vani; Irman, Irman; Yeni, Putri; Mohamed, Yassine (Yayasan Minang Darussalam, 2024)
The influence of the internet on juvenile delinquency is the focus of this research. In an era where digital connectivity is rampant, this research explores the positive and negative impacts of the internet on adolescent behavior. Intensive involvement in social media, exposure to controversial content, and online interactions can trigger juvenile delinquency. On the other hand, the internet also provides access to positive information and learning opportunities. This study details these complex dynamics to provide a holistic understanding of how the internet can shape adolescent behavior. Implications for policy development, educational approaches, and the role of parents in managing the impact of the internet on juvenile delinquency are also discussed as an integral part of this research.